1997
DOI: 10.1097/00007632-199712151-00005
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Osteoporosis and Vertebral Fracture

Abstract: The ability of the spine to carry load depends on the structural capacity of the vertebrae and on the loading conditions that arise from activities of daily living or trauma. The ratio of the load on the spine to the failure load of the bone is called the factor of risk, a value that indicates whether fracture is likely during a given activity. A high factor of risk can result from weak bone that has a low failure load or from a risk activity that generates a large force. The failure load of the vertebral body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
20

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(134 citation statements)
references
References 41 publications
3
111
0
20
Order By: Relevance
“…Biomechanically, a treatment-induced increase in strength protects from fracture by moving the bone over or away from its fracture threshold (i.e., the point at which the in vivo forces applied to the bone during a strenuous activity or fall exceed the strength of the bone). (24)(25)(26) In contrast, agerelated decreases in strength increase the risk of fracture by moving the bone closer to or below its fracture threshold. Mosekilde et al (27,28) estimated that ∼10% of vertebral strength is lost per decade, and this loss is exacerbated further in individuals with osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomechanically, a treatment-induced increase in strength protects from fracture by moving the bone over or away from its fracture threshold (i.e., the point at which the in vivo forces applied to the bone during a strenuous activity or fall exceed the strength of the bone). (24)(25)(26) In contrast, agerelated decreases in strength increase the risk of fracture by moving the bone closer to or below its fracture threshold. Mosekilde et al (27,28) estimated that ∼10% of vertebral strength is lost per decade, and this loss is exacerbated further in individuals with osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanically, any fracture that is prevented for a bone having a pretreated strength below its biomechanical fracture threshold would only be prevented if the increase in vertebral strength was sufficiently large to protect against the applied in vivo loads. (24)(25)(26)30) Patients having numerous and/or severe prevalent vertebral fractures are at increased risk of subsequent fracture, (31,32) presumably because they have reduced strength of multiple vertebrae from the biomechanical deterioration associated with systemic bone loss. Hence, it would be expected that a large percentage of patients with prevalent fractures have other vertebrae that are near or below their biomechanical fracture threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in the apparent density and the bone mineral density of trabecular bone typify ageing and osteoporosis. In many experimental studies, the maximum force during compression of vertebral specimens has been assessed, and the failure force has been related to the apparent density and geometric properties of the vertebrae [9]. Measurements have shown that much lower failure force accompanies ageing and severe osteoporosis.…”
Section: Resultsmentioning
confidence: 99%
“…These are considerations that affect the probability of a fracture occurring and have to be addressed in simulations of femoral neck fractures (Lotz et al 1995;Keyak et al 1998). Estimating physiological loads in the spine is more difficult (Myers & Wilson 1997), as a vast number of muscles and ligaments are interacting in order to provide stability, and there is currently no method available for the non-invasive quantification of muscle forces in vivo. Most often a simplified compression of an individual vertebra is simulated.…”
Section: Loading Conditionsmentioning
confidence: 99%